Evaluation of the COVID-19 testing strategy in PHC of a high-vulnerability health district in Brazil, 2020-2022 - Sandra Garrido de Barros; Thais Regis Aranha Rossi; Ana Clara de Rebouças Carvalho; Denise Nogueira Cruz; Sisse Figueiredo de Santana; Camila Ramos Reis; Laio Magno; Inês Dourado; Ligia Maria Vieira-da-Silva (BMC Public Health)
Abstract Background Considering the potential role of primary health care (PHC) in the response to COVID-19, a formative evaluation (FE) was carried out between December 2021 and February 2022 to understand its work process against COVID-19 in a high-vulnerability health district in Brazil, identifying the difficulties in carrying out tests and the best practices for the implementation of the intervention “Expansion of testing, quarantine, e-health and telemonitoring strategies to combat COVID-19 in Brazil” (TQT). Methods FEs are used to guide the implementation of health interventions. This FE was based on a situational diagnosis of the territories and PHC health units of the health district under study, with approximately 400,000 inhabitants, in which the TQT Project would later be implemented. A qualitative study was conducted based on 22 semistructured interviews and three focus groups (FGs) involving 19 PHC professionals. The interviews and FGs were analysed in terms of their thematic content. Results There was a lack of coordination in implementing actions; COVID-19 testing was concentrated in a few PHC units, generating work overload and weakness of other health programs in these units; the health units’ physical structure was inadequate, and human resources were insufficient; and no criteria were identified for defining the number of tests offered per day per unit. Conclusions The FE identified barriers to testing and supported the design of the TQT, including the adaptations needed to implement actions. The concentration of testing in a few units is an important barrier to access; it is suggested that testing actions should be deconcentrated in as many health units as possible.